Higher C-reactive protein/albumin ratio is a potential marker for predicting amputation in patients with diabetic foot infection - Li Zhang; Xufeng Gao; Meifang He; Wenyan Wang; Yuebin Zhao (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: Non-traumatic amputation resulting from diabetic foot infection (DFI) poses significant clinical and public health concerns. The C-reactive protein (CRP)/albumin ratio represents a combination of the infection level and nutritional status. This study investigated the relationship between the CRP/albumin ratio and amputation in patients with diabetic foot infections. Subjects and methods: Patients with a DFI of Wagner grade. 3 diagnosed between January 2020 and September 2023 were retrospectively analyzed. The association between the CRP/albumin ratio and amputation was explored using multivariable logistic regression modeling. Stratified analyses were also performed to ensure the reliability of the findings. Results: Of 301 enrolled patients, 226 underwent amputation and 75 did not. The amputation rate increased with a greater CRP/albumin ratio in the non-adjusted, minimally adjusted, and fully adjusted models, regardless of whether the CRP/albumin ratio was regarded as a categorical or continuous variable. Conclusion: An increased CRP/albumin ratio was associated with a greater risk of amputation in individuals with DFI.